Evaluation of major causes of road accidents along North–East Highway, Nigeria - Yero, Arafat Suleiman (Penerbit UTM Press, 2015)
A major road link in the North-Eastern region of Nigeria is the Bauchi – Maiduguri highway that is a 425 km road that links a section of the north east region to other regions of Nigeria. The goods and services to the region are basically transported by road. This has increased vehicular traffic that resulted in increased road accident rates over the years. It is paramount to investigate the major causes of vehicle accidents on this highway as much has not been done to investigate accident cases on the route. The five year accident record on that route was obtained from the Federal Road Safety Corp of Nigeria, the Nigeria Police traffic unit, and the Nigeria union of road traffic workers. The study indicated that speed violation by drivers and bad road conditions contributes greatly in the rate of accidents along the route. Hence the study recommends better road maintenance culture and more sensitization of the road users and enforcement of speed limits